Haploidentical bone marrow transplants for haematological malignancies using non‐myeloablative conditioning therapy and post‐transplant immunosuppression with cyclophosphamide: results from a single Australian centre. Issue 2 (12th February 2013) - Bilmon, I. A.; Kwan, J.; Gottlieb, D.; Kerridge, I.; McGurgan, M.; Huang, G.; George, B.; Hertzberg, M.; Bradstock, K. F.
Abstract Aims To demonstrate safety and efficacy of haploidentical bone marrow transplantation with non‐myeloablative conditioning and high‐dose post‐transplant cyclophosphamide in adult patients with leukaemia or lymphoma. Background Human leukocyte antigen haploidentical bone marrow transplantation is a treatment option in patients with haematological malignancies who have no available human leukocyte antigen‐matched donor but is limited by conditioning regimen toxicity, graft failure, relapse and graft‐versus‐host disease (GvHD). Methods Twelve patients, median age of 51 years, underwent transplantation with T cell replete bone marrow from a haplotype‐matched relative. The conditioning regimen consisted of cyclophosphamide, fludarabine and low‐dose total body irradiation. Post‐transplant immunosuppression consisted of a single dose of cyclophosphamide 50 mg/kg on day 3, followed by oral tacrolimus and mycophenolate mofetil. Outcomes reported are overall survival, engraftment and chimerism, toxicity, and clinical outcome. Results All patients had neutrophil recovery (median 14.5 days), and 11 of 12 had platelet engraftment (median 17 days). Two patients had autologous reconstitution. Seven of nine assessable patients had complete donor chimerism. Four patients had grades II‐III GvHD, and none had grade IV GvHD. Four patients developed limited stage chronic GvHD. Five patients with acute myeloid leukaemia relapsed. Two patients died of nonrelapse causes, both from other malignancies, and five patients remain alive and relapse free. Median overall survival was 324 days (range 88–1163). Conclusion This regimen is feasible and well tolerated in older patients with high‐risk leukaemia or lymphoma, with minimal short‐term toxicity and low rates of GvHD. The proportion of disease‐free survivors indicates a graft‐versus‐malignancy effect is present in survivors.